Two-Dimensional Synergistic Interfacial Orientation on Tin Oxide-Reinforced Cobalt Carbonate Hydroxide Heterostructures for High-Performance Energy Storage - Pugalenthiyar, Thondaiman; Raj, Chellan Justin; Manikandan, Ramu; Antonysamy, Dennyson Savariraj; Puigdollers, Joaquim; Kaya, Cengiz; Kim, Byung Chul (AMER CHEMICAL SOC, 2023)
A hierarchical cobalt carbonate hydroxide (CCH) nanostructure with outstanding electrochemical kinetics and structural stability for energy storage is largely unknown. Herein, we report tin oxide-functionalized CCH surface-enabled unique two-dimensional (2D) interlayered heterostructures that promote high conductivity with more electroactive sites to maximize redox reactions. A simple electrodeposition technique was utilized to construct the hierarchical 2D CCH electrode, while a surface-reinforced method was employed to fabricate the 2D interlayered SnO on CCH. The fabricated SnO@CCH-8 electrode showed a maximum areal capacity of 720 mC cm(-2) (specific capacitance of 515 F g(-1)) at a current density of 1 mA cm(-2) in 3 M KOH electrolyte. The obtained results indicate that the synergetic effect of SnO in the CCH network delivers an efficient charge transfer pathway to achieve high-performance energy storage. Moreover, SnO@CCH-8//AC was devised as a hybrid supercapacitor (HSC), ensuring a maximum specific capacitance of 129 F g(-1) and maximum specific energy and power of 40.25 W h kg(-1) and 9000 W kg(-1), respectively, with better capacitance retention (94%) even beyond 10,000 cycles. To highlight the excellent performance in real-time studies, the HSC was constructed using a coin cell and displayed to power 21 light-emitting diodes (LEDs).
Keywords: cobalt carbonate hydroxide; tin oxide; 2D interlayered; electrodeposition; hybrid supercapacitor; DENSITY-FUNCTIONAL THEORY; BATTERY-TYPE ELECTRODES; FACILE SYNTHESIS; SUPERCAPACITORS; EFFICIENT; MICROSPHERE; Science & Technology - Other Topics; Materials Science